Eating wild animals: Rewards, risks and recommendations - Grace, Delia; Bett, Bernard K.; Cook, Elizabeth A.J.; Lam, Steven; MacMillan, Susan; Masudi, Phyllis; Mispiratceguy, M.; Ha Thi Thanh Nguyen; Hung Nguyen-Viet; Patel, Ekta; Slater, Annabel; Staal, Steven J.; et al. (International Livestock Research Institute, 2024)
During the COVID-19 pandemic, prominent calls were made in the Global North to end the hunting, selling and eating of meat from wild animals. This report is a partial response to such calls, arguing that such a ban would be both impossible and arguably immoral to enforce due to the benefits wild meat provides for many millions of mostly poor communities. It also acknowledges the risks inherent in eating wild meat and recommends reshaping the wild meat trade in ways that 1) ensure it is sustainable and fair to poor and under-nourished populations of the Global South; 2) do not harm biodiversity or put endangered species at increased risk; 3) are safer for human, animal and environment health; and 4) are more humane.